The Impossible QALY and the Denial of Fundamental Measurement: Rejecting the University of Washington Value Assessment of Targeted Immune Modulators (TIMS) in Ulcerative Colitis for the Institute for Clinical and Economic Review (ICER) - Paul Langley (University of Minnesota Libraries Publishing, 2020)
All too often organizations embrace standards for health technology assessment that fail to meet the standards of normal science. A continuing puzzle is why the axioms of fundamental measurement are ignored by researchers such as the University of Washington Model Group in constructing lifetime cost-per-QALY claims. The University of Washington Model Group is not alone; it is an accepted article of faith that multiattribute utility scales can be manipulated as if they had ratio scale properties, which they do not. This commitment to pseudoscientific claims, embracing intelligent design rather than natural selection, is endorsed by professional groups such as ISPOR as well as by self-appointed arbiters of value assessment such as ICER. Perhaps the answer is peer pressure rather than ignorance of the axioms of fundamental measurement. More to the point, if you have been an advocate of imaginary simulations a Damascene epiphany creates both psychological and professional challenges. After all, if cost-per-QALY constructs are rejected, then it is difficult to see what options there are for those attempting to model cost-effectiveness claims. If it is just ignorance of the axioms of fundamental measurement then a reasonable question is why these axioms, readily available on any number of internet sites, are ignored in health technology assessment programs. The purpose of this commentary is to review the ICER September 11th 2020 evidence report in ulcerative colitis, with particular reference to ICER's responses to questions  raised in the public comment period on the measurement properties (or their absence) for utility scales; in this context the EQ-5D instruments. The critique pointed out that the utility scores had ordinal properties. ICER, without proof, disputed this statement asserting that health economists believed (or assumed) they were ratio scales. This is nonsensical. ICER has two options: first, to continue to believe that the EQ-5D instruments had ratio properties or second, to acknowledge that they indeed only had ordinal properties, rejecting their many modeled claims for pricing and access.  Not surprisingly, the possibility of a Damascene epiphany was rejected. ICER maintained its assertion that health economists, presumably all of them, believe or possibly just assume for analytical convenience that the EQ-5D-3L and similar measures are in fact on a ratio scale. This introduces a new concept in fundamental measurement: a ratio scale without a true zero but with negative values. ICER is quite prepared to admit that negative I-QALYs are possible and their lifetime cost-per-incremental I-QALY modelling can yield negative I-QALYs.   Article Type: Commentary